Data Mining and Artificial Intelligence in Digital Forensics - Aswathy.R; Dr. A. Sherin (The Bioscan, 2025)
The artificial intelligence of the data integration they can used for extracting the information on the important steps in the area of digital forensics, because it seeks to improving on the precision and effectiveness of the law enforcement investigations. Current trials at time include huge and intricate information that are used for the challenging for the current scientific treatments to navigate. The aforementioned database they can use for the finding the fundamental patterns and anomalies by through using methods of data mining include as division and clustering. The artificial intelligence methods the opposite simplifies the procedure of analysis and greatly enhances the rate of processing and precision of detection. This becomes particularly relevant with the artificial training and deep neural networks in the deep learning techniques. The present research they can used for examines the way of these methods exist in the scientific instances include as analysing network traffic, identifying malware, and internal surveillance. The artificial intelligence to enhance on the forensic tools to be operate higher than traditional ones in the multiple significant domains, based on the in-depth review of the research and individual scenarios. The machine learning methods used for the great services shows increased antivirus recognition precision, better recognition of network intrusions, as well as effective treat from within detection. This current research contrast evaluation shows the significant improvements with regard to metrics include as identification costs, clarity, and recall that artificial intelligence systems have rendered feasible. The main investigation of the challenges and constraints they can used for the identifying digital forensics in the mining data, to accessing the needs of great data and the demand of computer power and moral concerns. The analysing on the result to be indicate the relevance of combining data mining techniques with modern AI techniques in the expert forensics efforts. The research studies they can use for the suppliers make resources in the advanced strategies, ensure the secure implementation via suitable instruction and develop moral standards. In the years to come, studies ought to focus on creating the solid structures for the ethical application of the AI in digital forensics, exploring novel development include as cloud based and block chain approaches and overcoming on the present barriers to technological challenges. The effectiveness and productivity of the inquiries into digital forensics potential in to substantially boosted by these technological advances.